Hubungan Tipe Kepribadian Ekstrover dan Introver dengan Prokrastinasi Akademik Mahasiswa Kedokteran: Penelitian - Kesuma, Putri Zalika Laila Mardiah; Febriani, Ratika; Mundijo , Trisnawati; Ramadhani, Adelia (PT Kalbe Farma Tbk., 2026)
Background: Academic procrastination refers to the act of postponing the completion of crucial and scheduled tasks. This research seeks the relationship between personality types (introvert and extrovert) and academic procrastination. Methods: A quantitative descriptive approach with a cross-sectional design. The participants include students from the Faculty of Medicine (FK) at Muhammadiyah University (UM) in Palembang, from the 2020 and 2021 cohorts; 127 individuals fulfilled the inclusion and exclusion criteria. The sampling technique was a total sampling. The tools used in this study were the Eysenck personality questionnaire (EPQ) and the active procrastination scale (APS). Results: A sum of 83 respondents (65.4%) displayed an extrovert personality, while 44 respondents (34.6%) showed an introvert personality; 114 respondents (89.8%) demonstrated low levels of academic procrastination behavior, whereas 13 respondents (10.2%) reported high levels of academic procrastination. A bivariate analysis showed that the relationship between personality type and academic procrastination had a p-value of 0.765 (p > 0.05). Conclusion: No significant correlation between personality type and academic procrastination among medical students from the 2020 and 2021 cohorts at FK UM Palembang. Additional research is required to investigate other factors that may lead to academic procrastination in medical students.